2020
DOI: 10.3390/jcm9010225
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Minimal Targeted Biopsy Core Number per MRI Lesion for Improving Prostate Cancer Grading Prediction

Abstract: Background: To study the impact of MRI characteristics and of targeted biopsy (TB) core number on the final grade group (GG) prediction. Materials and Methods: The cohort was 478 consecutive patients who underwent radical prostatectomy (RP) after positive mpMRI (multiparametric magnetic resonance imaging) followed by fusion TB. Endpoints were the upgrading and concordance rates between TB and RP specimens. Results: Upgrading rate after TB was 40.6%. Patients with upgrading had lower PIRADS (Prostate Imaging-Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Using this approach, Calio et al showed a decrease in the upgrading rate from 18% in patients without saturation biopsy to 7% when saturation biopsy of the index lesion was performed ( p = 0.021) [ 20 ]. Furthermore, Ploussard et al showed that obtaining a minimum of 4 cores in the case of 3 PIRADS lesions and a minimum of 3 cores in the case of 4–5 PIRADS lesions can lead to a 30% reduction in the upgrading rate [ 21 ]. However, in current clinical practice, the urologist performing the systematic biopsy is not blinded to the MRI, and frequently, the systematic targeting becomes cognitive-guided.…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach, Calio et al showed a decrease in the upgrading rate from 18% in patients without saturation biopsy to 7% when saturation biopsy of the index lesion was performed ( p = 0.021) [ 20 ]. Furthermore, Ploussard et al showed that obtaining a minimum of 4 cores in the case of 3 PIRADS lesions and a minimum of 3 cores in the case of 4–5 PIRADS lesions can lead to a 30% reduction in the upgrading rate [ 21 ]. However, in current clinical practice, the urologist performing the systematic biopsy is not blinded to the MRI, and frequently, the systematic targeting becomes cognitive-guided.…”
Section: Discussionmentioning
confidence: 99%
“…Software-assisted elastic-fusion registration was preferred to the template method as it required fewer cores and was feasible under local anesthesia [13]. In this setting, we obtained a median number of four cores from the IT, which was recently demonstrated in a cohort of 478 PI-RADS 3 targets to be sufficient to control under grading [22].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there was a heterogenous number of targeted cores taken (2–10), potentially further contributing to missed csPC by TB. Studies have suggested the need for higher number of cores (greater than 2) for higher‐grade cancers 25,26 . Whilst this was the case, however, only 15 patients had two cores taken for TB and five patients had less than 12 cores taken for SB, given the small lesion size.…”
Section: Discussionmentioning
confidence: 99%